TANGGUNG JAWAB PARA PIHAK TERHADAP PEMELIHARAAN OBJEK JAMINAN ACTION FIGURE GUNDAM DALAM PERJANJIAN GADAI - Luthfi Naufal Setia (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2023)
A credit agreement followed by a guarantee creates an additional agreement. Pledge agreement which is one of the additional agreements with the presence of collateral objects. Collateral objects become a sign to guarantee the fulfillment of the achievements in the agreement. Gundam Action Figures that are collateral objects are objects that are categorized as toys/decoration that have economic value and are a little complicated to maintain so that this guarantee is not damaged or lost, it requires responsibility for its maintenance. The purpose of this research is to find out the responsibilities of the parties, both the pawn giver and the recipient for the maintenance of the Gundam action figure as a pawn collateral object. This study uses normative juridical methods that are qualitative in nature with statutory and conceptual approaches. With the results of research on the distribution of rights and obligations of the parties and the collateral objects are with the pawnbroker, he is responsible for the collateral objects that are lost or damaged due to his negligence by referring to the Civil Code.